Florida Pusley Biology and Control in Fruiting Vegetables, Cucurbits, and Small Fruits - Andrew MacRae (EDIS, 2010)
HS1172, a 3-page illustrated fact sheet by Andrew W. MacRae, describes this drought-resistant annual with hairy leaves and stems that is common in row middles, strawberry production fields, and organic mulch for highbush blueberries — classification, seedling identification, mature plant, management considerations, and classical control. Includes reference. Published by the UF Department of Horticultural Sciences, May 2010.